Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/1059924x.2016.1211053
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Poor Housing with Mental Health Among North Carolina Latino Migrant Farmworkers

Abstract: This analysis examines the associations of housing conditions with mental health among migrant farmworkers. Data are from a 2010 cross-sectional study conducted in 16 North Carolina counties. Interviews and housing inspections were completed with 371 farmworkers in 186 camps. Mental health measures included depression (Center for Epidemiological Studies-Depression, CES-D), anxiety (Personality Assessment Inventory, PAI), and alcohol misuse (AUDIT-C). Housing measures were number of people per sleeping room, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Several other risk factors and symptoms predictive of psychological distress in farmers have been identified by researchers, such as government policies [5,17,18,22,67,77], isolation [9,17,18,37,163], heavy workload [7,37], role conflict [7,16], time pressure [7,67,79], poor housing conditions [11,22,32,66], foot and mouth disease among livestock [57,61,80,164], coal and gas development [165,166], beef crisis [167,168], lower levels of mindfulness and farmers’ work ability [78]. Overall these risk factors were stated in almost 42% of the identified studies on farmers’ mental health.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other risk factors and symptoms predictive of psychological distress in farmers have been identified by researchers, such as government policies [5,17,18,22,67,77], isolation [9,17,18,37,163], heavy workload [7,37], role conflict [7,16], time pressure [7,67,79], poor housing conditions [11,22,32,66], foot and mouth disease among livestock [57,61,80,164], coal and gas development [165,166], beef crisis [167,168], lower levels of mindfulness and farmers’ work ability [78]. Overall these risk factors were stated in almost 42% of the identified studies on farmers’ mental health.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Farming is associated with a range of physical and mental health risks because of the hard work under challenging conditions [2]. Studies on mental health in farming communities around the world have identified several common risk factors, namely: commodity prices, debt, climate change, drought, overwork, government regulations, isolation, role conflict, time pressure, and poor housing [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Mora wanted to emphasize how depressive and anxious symptoms can lead to more alcohol or tobacco abuse; in fact, in this study among 370 farmworkers, 16.7% participants had substantial depressive symptoms (CES-D ≥ 10), 8.8% had substantial anxiety (PAI ≥ 27), and 50.1% had the potential for alcohol misuse (AUDIT-C ≥ 4). There was, however, a significant association between high depression scores and alcohol misuse, 21% of those that had a CES-D score of 10 or greater also had a score of 4 or greater in the Audit test (p = 0.02) [63].…”
Section: Alcohol and Nicotine Abusementioning
confidence: 88%
“…This is in part because barracks‐style housing is more likely be been hidden from the public’s view (Summers et al 2015, 2572). A poor housing situation for farmworkers can negatively affect their well‐being (Arcury et al 2012) and mental health (Mora et al 2016b). Examining housing‐related struggles sheds light on the structural vulnerabilities facing farmworkers (Summers et al 2015).…”
Section: Policy‐exacerbated Isolation Among Latina Farmworkersmentioning
confidence: 99%